Estimasi Populasi Tokek Rumah (Gekko gecko Linaeus 1758) di Kota Semarang, Kab. Boyolali, Kab. Grobogan - Margareta - Rahayuningsih; Amir - Hamidy; Awal - Riyanto (Badan Pengembang Konservasi UNNES, 2023)
The house gecko is currently a type of wild animal that is in great demand for commercial trade, especially for consumption of its skin, meat and bones, especially as an ingredient in the chemical industry and traditional medicine. Based on various facts found in the field, most wild animals caught and traded are caught from nature, not from captivity. Data states that the highest export quota for house geckos comes from Java and especially Central Java, including the largest contributors. While there are no reports of this species populations in Central Java. Therefore, the purpose of this study was to analyze the house gecko population in Central Java, especially in Grobogan, Boyolali, and Semarang cities. The research was conducted in November-December 2021. The research method was interviews and direct observation (Visual Encountered Survey). Interviews were conducted during the day, researchers visited residents' homes according to the questionnaire guide. Meanwhile, the direct meeting method is carried out at night starting at 19.00–22.00 WIB. The results of the extrapolation analysis of house gecko density in 3 (three) districts/cities showed a total of 290.95 geckos. The highest density is found in Boyolali Regency.